ChemInform Abstract: What Can Density Functional Theory Tell Us about Artificial Catalytic Water Splitting?. Issue 33 (19th August 2014) - Mavros, Michael G.; Tsuchimochi, Takashi; Kowalczyk, Tim; McIsaac, Alexandra; Wang, Lee‐Ping; Van Voorhis, Troy
Abstract Review: 91 refs